Divulgação científica nas redes sociais dos laboratórios de Física do campus de Abaetetuba: uma análise metodológica netnográfica - PEREIRA, Reinaldo de Lima (2023)
Scientific dissemination is currently standing out in the virtual environment, because due to the covid-19 pandemic, which killed about 14.9 million people, by the year 2020. And with the mass media, they mobilized to help in social isolation, causing the dissemination of scientific news through the internet quickly. Consequently, the teaching-learning process needed to adapt to remote teaching with the use of technologies available and accessible to students. In view of this, there was also a need to create virtual platforms on the pages of the Physics Laboratories of the Abaetetuba Campus, and on social networks such as Facebook and Instagram, in order to promote scientific dissemination. Initially, making the community aware of health care and passing on true information from reliable sources. Managing to cover approximately almost 30 thousand people. And with the creation of the LFCA pages, quality audiovisual materials made available on social networks began to be observed, it became necessary to devise strategies to engage the public closer to scientific culture. In this sense, in this work, materials were created for scientific dissemination, providing greater engagement and reaching an ever-increasing audience. The analysis of the reach of the pages created outside through netnographic studies, which made it possible to improve projects and dissemination strategies. Thus, it is possible to conclude that existing technologies, such as social networks, can be tools that contribute to decisionmaking, scientific dissemination and still allow the inclusion of all, thus becoming a great instrument for teaching and learning in the areas of science.